KARAKTERISTIK PASIEN PENYAKIT GINJAL KRONIK DI RUMAH SAKIT TARAKAN JAKARTA PADA TAHUN 2025 - Djaja, Tobias; Kumar, Bhanu; Winaktu, Gracia JMT (Jurnal MedScientiae, 2026)
Chronic Kidney Disease (CKD) is a growing global health problem, and understanding patient characteristics is essential for improving clinical management. This descriptive study analyzed 131 medical records of CKD patients at Tarakan General Hospital in 2025. Most patients were male (54.2%), with the largest age group being 60–70 years (29.8%) and the most common occupation being homemakers (32.1%). CKD stage 5 was the most prevalent (84.4%), and 67.2% of these patients underwent hemodialysis. The most common risk factor was hypertension (68.7%), followed by cardiovascular disease (51.1%) and diabetes mellitus (46.6%). The majority of patients had anemia (78.6%; mean hemoglobin 9.2 g/dL), normal potassium levels (55.7%), and low bicarbonate levels (66.4%). These findings provide a comprehensive overview of CKD patient characteristics at Tarakan General Hospital and can serve as a basis for improving clinical care and guiding future research.